THE REQUIREMENT TO IMPROVE CONDITION OF PATCHOULI OIL BUSINESS SYSTEM BY FUZZY APPROACH - Asep Mohamad Noor dan Machfud (Jurnal Teknologi Industri Pertanian, 2010)
ABSTRACT The improvement of patchouli oil business system is a complex process that should be reviewed holistically, both business process and value chain of patchouli oil aspects where the stakeholders are involved.  An effective strategy to improve the condition of business system is needed, that is required a fulfillment of certain requirement or necessary condition as well as the priority which are meet  consumers’ requirement which is usually expressed in fuzzy terms.   Integration of fuzzy stakeholders’ requirement with a necessary condition should be analyzed comprehensively. The objectives of this study was to identify priority of the requirement or necessary condition that should be fulfilled  in order to improve the condition of patchouli oil business system based on its relation with stakeholders requirement by applying fuzzy quality function deployment (fuzzy-QFD). The result showed that priority of necessary condition that should be fulfilled were trade transparency, annulment of speculative trading, good manufacturing practice, cluster approach, fair trading, fair and balance involvement, and good agricultural practice. For expert subjectivity reduction, it was suggested that the expert evaluation should be compared to or merged with more exact evaluation based on a measurement instrument. Keywords: fuzzy QFD, patchouli oil, condition of business system improvement.